UNDERUTILISED FRUITS: A POTENTIAL OF LOCAL FOOD RESOURCE - SRIVASTAVA R. (International Journal of Pharma and Bio Sciences, 2013)
The present investigation deals with the identification, documentation and ethnobotanical exploration with respect to food value of 27 underutilised edible fruits consumed by ethnic people of north-eastern terai region of U.P. Most of the plant species are of high economic, nutritious food potential. The database of these fruits may be helpful in bioprospection for achieving food security and environmental sustainability.